5p-4(9+7)=0

Simple and best practice solution for 5p-4(9+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5p-4(9+7)=0 equation:


Simplifying
5p + -4(9 + 7) = 0

Combine like terms: 9 + 7 = 16
5p + -4(16) = 0

Multiply -4 * 16
5p + -64 = 0

Reorder the terms:
-64 + 5p = 0

Solving
-64 + 5p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '64' to each side of the equation.
-64 + 64 + 5p = 0 + 64

Combine like terms: -64 + 64 = 0
0 + 5p = 0 + 64
5p = 0 + 64

Combine like terms: 0 + 64 = 64
5p = 64

Divide each side by '5'.
p = 12.8

Simplifying
p = 12.8

See similar equations:

| 5x=x+6 | | 2x=6x-3.4 | | 1=.25x-3 | | -2/3*-2/3-3/4(21/3)= | | -5(2p+2)-10=3(4p+8) | | h(x)=x^2-7x+6 | | (3+2i)(5-3i)=0 | | 4x^2-32=2x | | 6m-8=9m+1 | | x^2-9=-4*x+7 | | 0.66=log(x) | | 2cos^2x-6cosx-2=0 | | p^4-30p^2q+81q^2=0 | | 2x-16=3n+15 | | 23-2x=10+11x | | 8(1-4x)=40 | | X+30=7 | | 5d+8=2d | | y=x^3-7x^2-8x | | y=-20x^2-34x+36 | | (3+2i)-(4+3i)=0 | | a^2-af-132f^2= | | 3x+8+16=7x | | -6x+27=-4x+17 | | 0.14(y-8)+0.04y=0.02y-1.2 | | 20+0.05=15.15 | | 15-(3-4y)=(y+2) | | 2y^3+7=0 | | 7/n-1=9/n+1 | | -10x+62=-6x+34 | | 4x^2+43x+70=0 | | 5/n+1=6/n+5 |

Equations solver categories